2020
DOI: 10.2337/dc21-s008
|View full text |Cite
|
Sign up to set email alerts
|

8. Obesity Management for the Treatment of Type 2 Diabetes:Standards of Medical Care in Diabetes—2021

Abstract: The American Diabetes Association (ADA) “Standards of Medical Care in Diabetes” includes the ADA's current clinical practice recommendations and is intended to provide the components of diabetes care, general treatment goals and guidelines, and tools to evaluate quality of care. Members of the ADA Professional Practice Committee, a multidisciplinary expert committee (https://doi.org/10.2337/dc21-SPPC), are responsible for updating the Standards of Care annually, or more frequently as warranted. For a detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 123 publications
(73 reference statements)
1
70
0
1
Order By: Relevance
“…Since the publication of these trials, achieving remission of type 2 diabetes has been identified as a top priority by people with diabetes and their carers [ 13 ]. United Kingdom governments have recently included remission of type 2 diabetes in their long-term type 2 diabetes frameworks [ 14 , 15 ], and the American Diabetes Association (ADA) Standards of Medical Care has, for the first time, included guidance on prescribing very low calorie diets to improve glycaemic control and promote remission of diabetes [ 16 ]. The National Health Service (NHS) in England and Scotland are currently introducing the use of very low calorie diets for obese people with type 2 diabetes in routine clinical care [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of these trials, achieving remission of type 2 diabetes has been identified as a top priority by people with diabetes and their carers [ 13 ]. United Kingdom governments have recently included remission of type 2 diabetes in their long-term type 2 diabetes frameworks [ 14 , 15 ], and the American Diabetes Association (ADA) Standards of Medical Care has, for the first time, included guidance on prescribing very low calorie diets to improve glycaemic control and promote remission of diabetes [ 16 ]. The National Health Service (NHS) in England and Scotland are currently introducing the use of very low calorie diets for obese people with type 2 diabetes in routine clinical care [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss of at least 5% of baseline level in obese patients is clinically significant and improves several obesity-related cardio-metabolical complications, such as arterial hypertension, dyslipidemia, and impaired glucose metabolism (including prediabetes and T2DM) [ 10 , 11 , 12 ]. Pharmacological treatment is generally recommended in patients who did not present significant improvement after lifestyle modifications and BMI ≥ 30 kg/m 2 or ≥27 kg/m 2 , with excess weight-associated comorbidities such as diabesity [ 1 , 13 , 14 ]. Currently approved anti-obesity drugs are illustrated in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…GLP-1 RAs and sodium-glucose co-transporter type 2 (SGLT-2) inhibitors are usually the class of drugs preferred in managing diabesity in association with metformin due to their association with weight loss [ 13 , 15 ]. In the present article, we aim to review and highlight the existing literature on the effects of liraglutide in managing diabesity and excess-weight individuals without diabetes, emphasizing its role as a lower-glucose therapy with benefits on cardiovascular outcomes, weight reduction, and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Current nutritional treatment guidelines for adults with type 2 diabetes focus on improving glycemic control, body weight management and cardiovascular risk factors. Although these guidelines emphasize individualized nutritional therapy, recommendations generally promote healthy whole foods with high fiber content and low added sugars and refined grains [7,8]. With regard to NAFLD, dietary recommendations mostly follow guidelines for adults with obesity and/or type 2 diabetes with a focus on energy restriction and diet quality [9,10].…”
Section: Introductionmentioning
confidence: 99%